Mild-heat-inducible sequentially released liposomal complex remodels the tumor microenvironment and reinforces anti-breast-cancer therapy. (17th June 2020) - Qin, Yue; Liu, Tingting; Guo, Mengfei; Liu, Yuping; Liu, Congyan; Chen, Yan; Qu, Ding
Abstract : Heat-responsive drug release helps celastrol & STS-coloaded liposome activate the cascade of TME normalization and enhances the anti-tumor efficacy. Abstract : Increasing evidence indicates that the tumor microenvironment (TME) imposes various obstacles in response to chemotherapies. Sodium tanshinone IIA sulfonate (STS) has a validated ability to repair the unfavorable TME, providing a suitable environment for celastrol-based chemotherapy. However, remodeling TME still possesses enormous challenges for STS due to the difficulty in a controlled release at tumor sites. Gold nanorods (GNRs) capable of converting near-infrared (NIR) light into heat offer a promising trigger approach to regulate the local drug release. Here, we fabricated a gold nanorod-anchored thermosensitive liposomal complex co-loaded with STS and celastrol (G–T/C–L), which could sequentially release STS and celastrol upon NIR irradiation at 808 nm. When G–T/C–L reaches the sites, NIR illumination produces mild heat (∼43 °C) and thereby triggers a rapid release of STS in the initial stage, decreasing the level of tumoral blood vessels, collagen, cancer-associated fibroblasts, and Th2 type cytokines. In the subsequent stage, celastrol was unloaded to exert an anticancer effect under an activated TME. In proof-of-concept studies, the treatment of G–T/C–L with NIR illumination showed a significant improvement in anticancer efficacy both in vitro and in vivo but without conventional photothermal therapy-associated side effects. This study proposes photothermal-triggered technology to realize controlled drug release, enriching the application with combinational STS and celastrol in anti-breast cancer therapy.